Zviad Gamsakhurdia’s Government and Constitutional Problems in Georgia - Jikia, Levan (Actual Problems of Kartvelology, 2019)
Since 80s of the 20th century new stage of the national movement started in Georgia, the government of Soviet Georgia was not able to control the situation and actually two governments were established in Georgia. The soviet government of Georgia was forced to announce elections of Supreme Council on October 28, 1990 in which the electoral party “Round Table – Freedom of Georgia” won. The chairman of The Supreme Council of Georgia – Zviad Gamsakhurdia became a leader of the national movement. Zviad Gamsakhurdia’s government faced two alternatives – to pursue the constitution of the soviet Georgia adopted in 1978 or to declare the constitution 1921 of Democratic Republic of Georgia as restored. It is noteworthy that the constitution of Democratic Republic of Georgia did not include juridical mechanisms in order to defend from the constitution of the Soviet Union. Therefore Zviad Gamsakhurdia’s government left the constitution 1978 of Georgia into force and made several amendments to it. Imperial forces encouraged Abkhazian and Ossetian Separatists and the illegal decisions taken by them posed threats towards action of the constitution of Georgia in certain parts of the territory of the country. Zviad Gamsakhurdia’s government was forced to take some counter-measures that were reflected in the constitution of Republic of Georgia. Zviad Gamsakhurdia’s government managed to maintain territorial unity of Georgia though as a result of great efforts.